Local governments in Vietnam use seasonal climate and ten-day weather forecasts to co-develop tailored agricultural advisories to strengthen farm decision-making in ~70,000 farmers in the Mekong Delta - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
DeRISK Southeast Asia — a regional project by the Alliance and its partners — introduced a participatory process to provincial and district stakeholders for developing tailored seasonal and ten-day agroclimatic advisories for rice production. These were disseminated via targeted communication channels. About 70,000 farmers in Tien Giang Province used the agroclimatic information for agricultural decision-making (crop selection, planting date, soil preparation, water/nutrient management, pest/disease control, harvesting). The approach is now being scaled to six more provinces in the Mekong Delta.